Modifikasi Mesin Pengupas Pinang Belah Kering Model Thresher - Ari Kurniawan; Sukadi (LPPM Politeknik Jambi, 2022)
Modify the palm fruit thresher machine into a thresher model dry split betel nut peeler by testing the tool so that it can find out the constraints of the palm fruit thresher machine, and disassembling the components or parts to be modified, namely; cover, collection channel, blade and drive clutch. The cover is designed to function to be sturdy from the impact of areca nuts and is cylindrical. The reservoir channel is designed to allow the peeled betel nut to enter the drain pipe and the blower is in charge of blowing between the peeled betel nut and the seeds. The blade is designed to peel the dry split betel nut. The drive clutch is designed to function as a connector/breaker for the engine rotation to the shaft and plain concrete iron and bearings as a v-belt retainer. In the test with a capacity of 50 kg 1 day drying, peeled 40 kg and unpeeled 10 kg with an average time of 15 minutes is the best test. Therefore, we can conclude that the best peeling results from this dry split betel nut peeler machine are almost 80% peeled.